Vliv 3D modelování na projektování pozemních komunikací - Indruchová, Sára (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práce se věnuje tvorbě 3D modelu zaměřeného na dopravní stavby. Cílem je najít možné výhody a nevýhody v odlišném přístupu projektování. V teoretické části práce je porovnán rozdíl 3D modelu a BIM modelu, dále je zde poukázáno na přednosti ale i úskalí při modelování a využití modelu v praxi. Praktická část této práce obsahuje převedení vybraných stavebních objektů a stávajících inženýrských sítí z 2D dokumentace do 3D modelu. Jako podklad pro tvorbu slouží již zpracovaná výkresová dokumentace ve stupni DSP.

This diploma thesis is based on creating a 3D model focused on transport constructions. The aim of the thesis is to find certain advantages and disadvantages in different design approaches. The theoretical part compares the difference between the 3D model and the BIM model, the advantages and difficulties of modelling and the use of the model in practice are pointed out as well. The practical part of this work includes the transformation of chosen road constructions and existing enginerring network from the 2D to the 3D model. The main source is already existing drawing document in DPS level which serves as the basis for this thesis.
Impact of 3D modelling on road design
Keywords: 3D model; BIM; modelování silnic; datový standard; CDE; Společné datové uložiště; Autodesk Civil 3D; liniová stavba; D35; PPP; 3D model; BIM; road modeling; data standard; CDE; Common data environment; Autodesk Civil 3D; linear construction; D35; PPP